Mutual fund regulation in Indonesia: protection for investor - Anam, Samsul (2016)
Mutual fund industry in Indonesia has grown dramatically since launched in 1996. The bigger mutual fund industry in a country concequenly has bigger potency of problems. One of the example of problem in mutual fund industry can be seen on mutual fund scandals happened in 2003 in USA. The potency of problem in mutual fund industry can come in investor protection point of view. The investor protection in mutual fund industry can be ensured by existance of government regulations. Investor protection can be categories based on eight categories of activitiy. Those are solvency, independency, competency, communication, cancellation and compensation, market abuse and insider dealing, money laundering, and pricing. Based on those eight categories of activies and lesson learn from mutual fund scandals happened in 2003, the researcher try to understand how investor protection in Indonesia mutual fund industry are. Based on our analysis, the regulation of mutual fund industry meets precisely seven categories of activity, namely solvency, independency, competency, communication, market abuse and insider dealing, money laundering, and pricing. One category of activity that does not match precisely is cancellation and compensation activity. Indonesian government through its agency, Indonesia Financial Service Authority, does not regulate cancellation and compensation category. Indonesian government, as a result, conducts another way to protect investor from misinformation and wrong advice from mutual fund advisor or salesman. Learn from mutual fund scandals happened in 2003, Indonesia has implemented several regulations to avoid this scandals happen in Indonesia.